Modeling of remote backup system - Chan, Kwun Hok. (2009)
Chances are you have a lot of important stuffs on your computer like documents, reports, emails, photos, music and many more. Unfortunately, computers are very vulnerable to hard drive crashes, virus attacks, theft and natural disasters, which can cause data lost in an instant. Therefore data backup is definitely needed to protect these important stuffs. With the volume of data increasing everyday, data backup has become a tedious task for many people. Remote backup system is an application system whereby it automates the backup process for the user. Data is being backed up to a remote site, usually offered by a service provider. On the remote site, the administrators or engineers will perform data protection to ensure near-zero data loss in the event of a disaster. This report describes the development of a practical model to be used in remote backup systems for consumer.